You say regulation, I say punishment: the semantics and attributes of punitive activity - Lucken, Karol (Critical criminology, 2013)
Recent trends in crime control have given new energy to an age-old question, namely what kinds of activity qualify as punishment. In addressing this question, jurists and scholars have often employed a logic that either restricts interpretations of punishment to traditional forms (e.g., prison, probation, death penalty) and functions (e.g., deterrence and retribution), or expands them to include the broader forms and functions of social control. This paper examines these opposing logics and considers an alternative logic based in common stipulations in power theory. Within this particular framework, punishment is conceived as action that is necessarily relational, intentional, personal and coercive.